Maternal outcomes of planned mode of delivery for term breech in nulliparous women - Caning, Malene Mie; Rasmussen, Steen Christian; Krebs, Lone (PloS one, 2024)
To estimate short- and long-term maternal complications in relation to planned mode of term breech delivery in first pregnancy. Register-based cohort study. Denmark. Nulliparous women with singleton breech delivery at term between 1991 and 2018 (n = 30,778). We used data from the Danish national health registries to identify nulliparous women with singleton breech presentation at term and their subsequent pregnancies. We performed logistic regression to compare the risks of maternal complications by planned mode of delivery. All data were proceeded and statistical analyses were performed in SAS 9.4 (SAS Institute Inc. Cary, NC, USA). Postpartum hemorrhage, operative complications, puerperal infections in first pregnancy and uterine rupture, placenta previa, post-partum hemorrhage, hysterectomy and stillbirth in the subsequent two pregnancies. We identified 19,187 with planned cesarean and 9,681 with planned vaginal breech delivery of which 2,970 (30.7%) delivered vaginally. Planned cesarean significantly reduced the risk of postoperative infections (2.4% vs 3.9% adjusted odds ratio (aOR): 0.54 95% confidence interval (CI) 0.44-0.66) and surgical organ lesions (0.06% vs 0.1%; (aOR): 0.29 95% CI 0.11-0.76) compared to planned vaginal breech delivery. Planned cesarean delivery in the first pregnancy was associated with a significantly higher risk of uterine rupture in the subsequent pregnancies but not with risk of postpartum hemorrhage, placenta previa, hysterectomy, or stillbirth. Compared to planned vaginal breech delivery at term, nulliparous women with planned cesarean breech delivery have a significantly reduced risk of postoperative complications but a higher risk of uterine rupture in their subsequent pregnancies.